Q. 6 A4.0( 4 Votes )

# Apply Division Algorithm to find the quotient q(x) and remainder r(x) on dividing p(x) by g(x) as given below:

p(x) = 2x^{2} + 3x + 1, g(x) = x + 2

Answer :

p(x) = 2x^{2} + 3x + 1, g(x) = x + 2

Dividend = 2x^{2} + 3x + 1,

Divisor = x + 2

Apply the division algorithm we get,

q(x) = 2x – 1

r(x) = 3

Rate this question :

Divide the polynomial p(x) by the polynomial g(x) and find the quotient q(x) and remainder r(x) in each case :

p(x) = x^{3} – 3x^{2} + 4x + 2 , g(x) = x – 1

Divide the polynomial p(x) by the polynomial g(x) and find the quotient q(x) and remainder r(x) in each case :

p(x) = x^{3} – 3x^{2}– x + 3, g(x) = x^{2} – 4x + 3

When a polynomial p(x) is divided by (2x + 1), is it possible to have (x - 1) as a remainder? Justify your answer.

RS Aggarwal - MathematicsDivide the polynomial p(x) by the polynomial g(x) and find the quotient q(x) and remainder r(x) in each case :

p(x) = x^{4} + 2x^{3} – 3x^{2} + x – 1, g(x) = x – 2

Find all the zeroes of the polynomial given below having given numbers as its zeroes.

x^{4} – 6x^{3} – 26x^{2} + 138x – 35;2±√3